The efficacy and safety of phototherapy in geriatric patients: a retrospective study - Isil Bulur; Hilal Kaya Erdogan; Ayse Esra Aksu; Tekden Karapınar; Zeynep Nurhan Saracoglu (Sociedade Brasileira de Dermatologia, 2018)
Abstract: Background: While phototherapy is a well-established treatment for many dermatoses, data from the literature regarding its use in elderly patients are quite limited. Objective: In this study, we aimed to determine the phototherapy indications in geriatric patients and to evaluate the effectiveness and reliability of phototherapy in this group. Methods: This study included 95 patients of 65 years of age and older who were treated in our phototherapy unit between 2006 and 2015. The data for this study were collected retrospectively from patient follow-up forms in the phototherapy unit. Results: Phototherapy was administered to 28 (29.5%) patients for mycosis fungoides, 25 (26.3%) patients foplaque type psoriasis, 12 (12.6%) patients for palmoplantar psoriasis, 12 (12.6%) patients for generalized pruritus, and 18 (19%) for other dermatoses. Of the patients, 64.2% had received a narrowband UVB (NB-UVB), 21.1% oral psoralen UVA (PUVA), and 14.7% local PUVA treatment. A complete response was achieved in 76.9-85.7% of the mycosis fungoides and in 73.71-100% of the psoriasis vulgaris patients treated with NB-UVB and PUVA, respectively. All the patients with generalized pruritus were treated with NB-UVB, and 80% of these patients achieved significant improvement. The erythema rate was found to be 0.43% per session for NB-UVB treatment and 0.46% per session for PUVA treatment as a side effect. Study limitations: The limitations of our study are that it was retrospective and the remission durations of the patients are not known. Conclusion: This study showed that phototherapy is effective and reliable in the elderly population with proper dose increases and close follow-up.